The structure of CLEC-2: mechanisms of dimerization and higher-order clustering. (18th August 2021) - Martin, Eleyna M; Zuidscherwoude, Malou; Morán, Luis a; Di, Ying; García, Angel; Watson, Steve P
Abstract: The platelet C-type lectin-like receptor CLEC-2 drives inflammation-driven venous thrombosis in mouse models of thrombo-inflammatory disease with a minimal effect on hemostasis identifying it as a target for a new class of antiplatelet agent. Here, we discuss how the protein structure and dynamic arrangement of CLEC-2 on the platelet membrane helps the receptor, which has a single YxxL motif (known as a hemITAM), to trigger intracellular signaling. CLEC-2 exists as a monomer and homo-dimer within resting platelets and forms higher-order oligomers following ligand activation, a process that is mediated by the multivalent nature of its ligands and the binding of the tandem SH2 domains of Syk to the phosphorylated hemITAM and concomitantly to PIP2 or PIP3 to localize it to the membrane. We propose that a low level of active Syk is present at the membrane in resting platelets due to phosphorylation by Src family kinases and that clustering of receptors disturbs the equilibrium between kinases and phosphatases, triggering phosphorylation of the CLEC-2 hemITAM and recruitment of Syk. Knowledge of the structure of CLEC-2 and the mechanism of platelet activation has important implications for development of therapeutics.